Facilitative practices to promote migrant children's agency and hybrid integration in schools: discussing data from Italy, Poland and England. (4th March 2023) - Baraldi, Claudio; Farini, Federico; Ślusarczyk, Magdalena
ABSTRACT: This paper discusses the interactional construction of personal trajectories of migrant children with a focus on its implications for the enhancement of children's agency. The discussion is supported by the analysis of three extracts transcripts of audio or video-recorded classroom activities that illustrate the main forms of facilitation of migrant children's agency as authorship of narratives of personal trajectories of migration, also showing that facilitation is influenced by children's language proficiency. The construction of narratives can be context for the negotiation of hybrid integration, at the intersection between forms of facilitation, social and cultural contexts and personal trajectories and experiences.